Informatisation of the Educational Environment of Higher Educational Institutions: Priorities and Development Deficits - Savitska, Viktoriia; Koruts, Uliana; Trawnih, Ali; Petrovič, František; Majda , Peter; Kovalcikova, Renata (Journal of Education Culture and Society, 2026)
Aim. The aim of the study is to examine lecturers' attitudes toward the state of the information and educational environment in modern higher education institutions and their readiness to implement modern digital technologies in the educational process.Methods. This study involved 150 lecturers, whose teaching experience ranged from 1 to 25 years, and participation was voluntary. The key method used was a questionnaire survey, the tools of which revealed the specifics of the content of the information and educational environment and reflected the lecturers' perception of the possibilities of didactic means based on information technologies, as well as the shortcomings in the development of the modern information and academic environment of higher education.Results. Based on empirical study identified the content and information-related organisational issues of the academic environment of higher education institutions. The authors also identified barriers to the development of the information and educational environment. They include insufficient material and technical equipment, a lack of digital competence among lecturers, and a limited use of interactive technologies.Conclusions. The informatisation of the educational process is aimed at the creation and optimal use of software, technological, and instructional-methodological developments. The implementation of didactic learning tools based on digital technologies will be more effective if an appropriate set of resources is developed for each discipline. The active integration of information technologies into the educational process leads to a significant transformation of teachers’ roles toward those of researchers, organizers, consultants, and facilitators.